Reconstruction of Integrative Islamic Epistemology: Analysis of the Implementation of Yani, Irfani, Burhani, and Illumination - Nurzamsinar; Sudirman; Abd. Wahid (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to propose an integrative Islamic epistemological model that harmonizes the bayani, ʿirfani, burhani, and illumination (hikmah al-isyraq) approaches to address the fragmentation of modern knowledge in Islamic education. The literature gap lies in the absence of a comprehensive epistemological model that harmonizes revelation, reason, and intuition as a unified basis for Islamic education and scientific inquiry. This study employs a qualitative approach with library research methods, systematically analyzing classical and contemporary theories in Islamic epistemology through thematic tafsir, turath analysis, and Islamic hermeneutics. The main findings indicate that revelation (wahy) constitutes the primary and irreducible source of knowledge, which should govern and guide the integration of reason and intuition in educational practice and research. The proposed model synthesizes these four paradigms into a coherent framework anchored in tawhid and adab, offering both philosophical depth and operational applicability. Scientifically, this study contributes by unifying the rational, spiritual, and intuitive dimensions of knowledge to address the challenges of contemporary Islamic education. Practical implications include the development of a holistic Islamic education curriculum that integrates revelation as the epistemological foundation, as well as the application of this model in social, scientific, and institutional contexts relevant to current global developments in Islamic thought and education.